Image Concerns and the Provision of Quality - Jana Friedrichsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Consumption patterns can be indicative of how a consumer wants to be perceived by others. In this paper, I study markets where consumers are heterogeneous with respect to both their concerns for the quality of goods and the image associated with buying them. Consumers with a taste for quality lend a positive image to the product of their choice and thereby increase the product's value to others. A monopolist restricts the product portfolio and charges price premia to allocate image along with quality. Heterogeneity in image concerns thereby provides a rationale for pooling consumers with differing quality preferences. Although image is correlated with a product's quality in equilibrium, an increase in the value of image may decrease quality provision. In a competitive market, premium prices are unsustainable so that image-concerned consumers buy excessive quality instead. By restricting the product space, monopoly allows for more efficient allocation of image and may therefore yield higher welfare than competition. Policy options to remedy the efficiency losses are discussed.
Keywords: D21; D82; L15; 330